2021
DOI: 10.5194/os-2021-1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Progress in understanding of Indian Ocean circulation, variability, air-sea exchange and impacts on biogeochemistry

Abstract: Abstract. Over the past decade, our understanding of the Indian Ocean has advanced through concerted efforts toward measuring the ocean circulation and its water properties, detecting changes in water masses, and linking physical processes to ecologically important variables. New circulation pathways and mechanisms have been discovered, which control atmospheric and oceanic mean state and variability. This review brings together new understanding of the ocean-atmosphere system in the Indian Ocean since the las… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 708 publications
(708 reference statements)
0
7
0
Order By: Relevance
“…The South Equatorial Current (SEC) is a key current in the tropical SIO (Phillips et al., 2021; see also the schematics in the sixth panel of Figure 1). Ship‐drift (e.g., Cutler & Swallow, 1984) and drifters data (Shenoi et al., 1999) have shown that the SEC is a band of westward flow between 10°S and 20°S extending across the SIO basin.…”
Section: Introductionmentioning
confidence: 99%
“…The South Equatorial Current (SEC) is a key current in the tropical SIO (Phillips et al., 2021; see also the schematics in the sixth panel of Figure 1). Ship‐drift (e.g., Cutler & Swallow, 1984) and drifters data (Shenoi et al., 1999) have shown that the SEC is a band of westward flow between 10°S and 20°S extending across the SIO basin.…”
Section: Introductionmentioning
confidence: 99%
“…Even though ocean current patterns and circulations are mostly similar all-around years, the Indian Ocean circulation pattern varies by inter-annual variability (Schott et al, 2009 andPhillips et al, 2021). The simulation year of 2015 noticed that the peak current can reach more than 80 cm.s -1 in some months.…”
Section: Discussionmentioning
confidence: 96%
“…The physical oceanography of the northern Indian Ocean reflects the seasonal changes in the monsoon cycle, including impacts on currents, thermohaline circulation, sea surface temperature (SST), salinity, and upwelling events, while the equatorial and southern Indian Ocean does not experience this influence. For more details about general Indian Ocean physical processes, please see Schott et al (2009) and references therein, Phillips et al (2021) from this issue, and Sect. S2.…”
Section: Oceanic Processesmentioning
confidence: 99%